Predictors of word writing in Spanish and Arabic among 6- and 7-year-old children - González-Valenzuela, María José; Lopez-Montiel, Dolores; Chebaani, Fatma; Cobos-Cali, Marta; Piedra-Martínez, Elisa; Martín-Ruiz, Isaías (Springer, 2024)
This study analyses the impact of certain cognitive processes on the writing of words in languages with different orthographic consistency (Spanish and Arabic) in the first and second years of Primary Education. One hundred twenty-eight schoolchildren from Ecuador and 109 from Algiers participated in this study. All the participants were aged between 6 and 7 years old, came from the middle classes, and had no special educational needs. We evaluated all the participants for word writing, knowledge of letters, phonological awareness, rapid automatised naming (alphanumeric and non-alphanumeric), and phonological memory. We performed descriptive-exploratory analyses and bivariate and multivariate regressions for the writing of words in each language. The results show that most of the cognitive variables considered do not contribute equally to the explanation of word writing in both languages at 6 and 7 years of age. However, in each language, at these ages, similar variables contribute to the explanation of word writing. These results have important implications for educational practice, as well as the explanatory theory of writing acquisition.
Keywords: Escritura - Estudio y enseñanza; Writing; Cognitive predictors; Spanish; Arabic